Definitions, importance, and application of selective mutism questionnaire in the primary care setting - Esmail, Mustafa E.; Alharbi, Manar B.; Alayed, Ibrahim S.; Alqahtani, Mohammed S.; Aldeeb, Hassan F.; Alanazi, Yazeed H.; Almasoud, Hassan A.; Almohaimeed, Omar A.; Alharthi, Suhail M.; Alsuhaiman, Yousef H.; Doshi, Tahani A. (International Journal Of Community Medicine And Public Health, 2021)
Children with selective mutism might suffer from less frequent involvement in school activities, reduced social and cognitive abilities, in addition to being at increased risk of subjective suffering and developing other associated morbidities. There is a lack of evidence regarding the assessment modalities that should be used to evaluate selective mutism. However, recent data show that the selective mutism questionnaire (SMQ) is validated among different investigations with well-established psychometric properties. In the present literature review, we have discussed the definition, uses, and importance of the SMQ for children with selective mutism in primary care settings. Our results show that the different included studies indicate the sensitivity and reliability of the tool to assess the severity of behavioral speaking among these children. Besides, evidence has shown that the tool can be used to assess the impact of treatment on the behavioral outcomes of these children. Based on these data, it has been demonstrated that the treatment of selective mutism can significantly enhance the scores and the behavioral speaking patterns. However, these scores were still relatively lower than the ones estimated for the typically developing children. The impact of more intensive treatment modalities has been suggested but was not adequately validated, and therefore, further research is a must for adequate interpretation and validation of the current findings to achieve better outcomes.